Peran Pembiayaan Mudaharabah dalam Meningkatkan Kinerja Usaha Kecil Menengah pada BMT (Baitul Maal Wa Tamwil) - Ahmad Rama Wijaya (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Increasing the performance of small businesses can be done by using several elements such as coaching and supervision. Mudharabah financing is very suitable for micro businesses. Therefore, mudharabah financing is expected to play a role in developing micro business performance. This article was written based on a literature review of previous literature and research in the field of sharia financing to develop a model. There are several factors that support the success of mudharabah financing at BMT in developing micro business performance.